2006
DOI: 10.1590/s0100-879x2006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Decision support system for the diagnosis of schizophrenia disorders

Abstract: Clinical decision support systems are useful tools for assisting physicians to diagnose complex illnesses. Schizophrenia is a complex, heterogeneous and incapacitating mental disorder that should be detected as early as possible to avoid a most serious outcome. These artificial intelligence systems might be useful in the early detection of schizophrenia disorder. The objective of the present study was to describe the development of such a clinical decision support system for the diagnosis of schizophrenia spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Razzouk et al [9] developed a decision support system for the diagnosis of schizophrenia disorders with an accuracy of 66-82%. Chattopadhyay et al [10] developed a neuro-fuzzy approach to grade adult depression.…”
Section: Related Workmentioning
confidence: 99%
“…Razzouk et al [9] developed a decision support system for the diagnosis of schizophrenia disorders with an accuracy of 66-82%. Chattopadhyay et al [10] developed a neuro-fuzzy approach to grade adult depression.…”
Section: Related Workmentioning
confidence: 99%
“…The current trend and future applications and their implications have been discussed. Razzouk D., et al [9] developed a decision support system for the diagnosis of schizophrenia disorders with an accuracy of 66-82%. Chattopadhyay S., et al [10] developed a neurofuzzy approach to grade adult depression.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the approach greatly reduced the demand on therapist's time, it lacked the patient -doctor feedback mechanism which is crucial for depression therapy. In Razzouk, Mari, Wainer, & Sigulem (2006), a pilot study for modeling the diagnoses of schizophrenia and other psychotic disorders is reported. In Mila et al (2009), a fuzzy semiotic framework for modeling imprecision in the assessment of depression is presented.…”
Section: Related Workmentioning
confidence: 99%